Feasibility, effectiveness, and safety of endoscopic vacuum therapy for intrathoracic anastomotic leakage following transthoracic esophageal resection - Zhang-Hagenlocher, Christine; Liesenfeld, Lukas; Klotz, Rosa; Koschny, Ronald; Rupp, Christian; Schmidt, Thomas; Diener, Markus K.; Müller, Beat P.; Hackert, Thilo; Sauer, Peter; Büchler, Markus W.; Schaible, Anja (BMC gastroenterology, 2021)
Anastomotic leakage (AL) in the upper gastrointestinal (GI) tract is associated with high morbidity and mortality rates. Especially intrathoracic anastomotic leakage leads to life-threatening complications. Endoscopic vacuum therapy (EVT) for anastomotic leakage after transthoracic esophageal resection represents a novel concept. However, sound clinical data are still scarce. This retrospective, single-center study aimed to evaluate the feasibility, effectiveness, and safety of EVT for intrathoracic anastomotic leakage following abdomino-thoracic esophageal resection.
Gesehen am 10.09.2021